Plant identification using model reference techniques - Camara, C D J (Department of Electrical Engineering, 2026)
Adaptive control is a branch of control which came to the fore in the early 1950's. It evolved due to the necessity of a systematic technique for the design of optimal control systems when the dynamic characteristics of the plant under consideration are poorly known or. when the plant is subjected to large and unpredictable variations. The basic principal behind adaptive controllers is the continual adaptation of the controller parameters in order to n~ll the effect of drift variations which may occur in the dynamic characteristics of the plant under consideration. It is this elimination of the effect of drift variations upon the performance of the control system, which makes adaptive control such an attractive scheme as compared to the classical feedback control methods. A special branch of adaptive systems known in the literature as Model Reference Adaptive Systems (MRAS'S), evolved in the late 1950's. A MRAS is an adaptive system which operates to null an error between the plant under consideration and a model by adapting the characteristics of the model.